Determinants of uptake of home modifications and exercise to prevent falls in community‐dwelling older people - Lara A. Harvey; Rebecca J. Mitchell; Stephen R. Lord; Jacqueline C.T. Close (Australian and New Zealand Journal of Public Health, 2014)
Abstract Objective: To examine the age‐specific population prevalence and predictors of uptake of home modifications and exercise to prevent falls in the NSW older population. Methods: A total of 5,681 respondents were asked questions on fall prevention activities as part of the 2009 NSW Falls Prevention Survey. Results were weighted to represent the NSW population. Regression analysis was used to determine factors associated with uptake of interventions. Results: Overall, 28.9% of the older population have modified their home, and 35.1% increased exercise to prevent falls. Main predictors of home modification were being aged 85+ (RR 2.04, 95% CI 1.76–2.35) and physiotherapy/occupational therapy intervention (RR 1.57, 95% CI 1.22–2.01). Main predictors of increasing exercise were physiotherapy/OT intervention (RR 2.12, 95% CI 1.86–2.42) and medical advice (RR 1.45, 95% CI1.32–1.60). Older respondents (RR 0.68, 95% CI 0.57–0.81) and those with fair/poor health (RR 0.86, 95% CI 0.77–0.96) were less likely to report increased exercise. Conclusion: More than one‐quarter of the older population of NSW report having made modifications to their home and one‐third increased exercise to prevent falls. There was a clear gradient of increased uptake of home modifications with increasing age, with the reverse trend for increased exercise. Implication: Although fall prevention initiatives are having an impact at the population level, targeted strategies for high‐risk groups are still required.